Legal Obligation of Researchers to Have a Research Certificate According to Minister of Home Affairs Regulation Number 3 of 2018: Violation of the Right to Freedom of Opinion and Obligation to ADVANCE Science - Herman, Ronaldo Heinrich (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
are still not fulfilled with the enactment of Regulation of the Minister of Home Affairs of Republic Indonesia No. 3 Year 2018 which requires every researcher to have a Research Certificate. Complicated procedures and lack of clarity regarding the negative impacts that could arise from the research are factors that prevent researchers from obtaining the letter. As a result, the amount of research will decrease and the rights of every person in Indonesia to benefit from developments in science and technology will be violated. These restrictions also violate researchers' rights to freedom of expression through their research. In this normative legal research, the author intend to analyze how the provisions of Regulation of the Minister of Home Affairs of Republic Indonesia No. 3 Year 2018 violate the rights of researchers and everyone in Indonesia as well as the solution in the form of revoking these provisions and setting new laws and regulations that better accommodate these human rights. The data in this research was obtained through document studies of statutory regulations, books, journal articles, legal dictionaries, and related news from the internet.